More than a Man, Less than a Painter: David Smith in the Popular Press, 1938–1966 - Paula Wisotzki (Arts, 2023)
Media coverage was vital in establishing the popular reputation of the Abstract Expressionists. Reporting regularly relied on photographic portraits to present these artists as modernist innovators who were an extension of (or even a replacement for) the work of art. Jackson Pollock came to epitomize the Abstract Expressionist artist, with “action” photographs capturing his radical painting method. Pollock’s contemporary, American sculptor David Smith, similarly transformed his medium—in his case by embracing industrial methods to make three-dimensional objects. However, given the constraints inherent in the process of welding he employed, how could Smith’s image be reconstituted as a celebration of artistic individuality so crucial to modernism? The very method Smith embraced to push the boundaries of art kept him from representing the genius creator who channeled the forces of nature to produce culture. By tracing photographs documenting his career published in local and regional newspapers, popular magazines from Popular Science to Life, and mass art magazines from Magazine of Art to Arts, this paper demonstrates that images of Smith at work as an anonymous industrial worker enveloped in protective gear were regularly balanced with images of contemplation—the traditional image of the artist as mediating intelligence. Yet, over the years of his career, the problem of representing Smith was addressed somewhat differently. Early on, there was a tendency to show Smith applying his novel art-making techniques to the production of more traditional objects. During World War II, when Smith was employed as a commercial welder, Smith the artist legitimized reporting on Smith the worker. Finally, in the post-war world—as Smith benefited from the burst of publicity surrounding the triumph of Abstract Expressionism—his rigorous manipulation of metal was celebrated as masculine display, effectively shifting attention away from common industrial labor to heroic individual struggle.